Assessment of antipsychotic-induced cytotoxic effects on isolated CD1 mouse pancreatic beta cells - Al Doghaither, Huda A.; Elmorsy, Ekramy M. (International Journal of Health Sciences, 2023)
Objectives: The study aims to assess apoptosis, oxidative stress, and inflammation as underlying diabetogenic mechanisms in isolated CD1 mouse beta-pancreatic cells of some prescribed Antipsychotics (APs). Methods: Three types of APs were tested in different concentrations (0.1, 1, 10, and 100 μM) on adult male CD1 mice. The cytotoxicity of the tested APs was determined using different assays including MTT and Lactate Dehydrogenase (LDH) assays. Oxidative stress was assessed by and measuring Reactive oxygen species (ROS) production, lipid peroxidation, and antioxidant enzyme activities. Moreover, the effect on the inflammatory cascade was also investigated. Results: The tested APs were cytotoxic to beta cells and showed patterns dependent on both concentration and exposure, with a parallel reduction in glucose-stimulated insulin secretion of the treated cells. The APs also showed induction of oxidative stress in the treated cells by significantly increasing the ROS, lipid peroxidation, and NRf2 gene expression, together with decreased antioxidant enzyme activities. Moreover, APs showed significant increases in cytokines levels to their estimated IC50 levels. The activities of caspases 3, 8, and 9 were also significantly increased in all treated samples at their IC50s and at 10 μM concentrations of all tested APs. However, the glutathione and inhibitors of caspase-3, IL-6, and TNF-α significantly improved GSIS and the viability of the AP-treated cells. Conclusion: The results suggest a significant role for apoptosis, oxidative stress, and inflammation, in the diabetogenic effect of APs, expected role of antioxidants and anti-inflammatory drugs as therapeutics for improving the outcome in cases of long-term prescribed APs.